ANALYSIS OF THE PHYSICAL CONDITION OF THE ACEH PON RUGBY ALTET 2021 - Tuti Sarwita; Zulheri Is; Septi Hariansyah (Teunuleh Publisher, 2021)
Rugby is one of the most popular sports abroad. Rugby sport that must have good physical condition for every athlete. The purpose of this study was to determine the level of physical condition of the Aceh PON team rugby athletes. With this type of quantitative descriptive research, the sample in this study was the Putra Pon Aceh Rugby Team as many as 12 athletes. Based on the results of the research on the physical condition test of the endurance level of athletes, the physical condition of the Aceh PON Rugby players was in the